The modifying effect of dietary index for gut microbiota on the association between urinary arsenic exposure and bladder cancer risk: a nationwide cohort study - Sun, Lingfeng; Liu, Chengyi (Frontiers in Nutrition, 2025)
ObjectiveArsenic exposure is a well-established risk factor for bladder cancer, but substantial individual variability in susceptibility suggests the potential role of effect modifiers. The gut microbiome, which is influenced by diet, may regulate arsenic metabolism and toxicity. The Dietary Index for Gut Microbiota (DIGM) quantifies the potential of diet to foster a beneficial gut ecosystem, yet its role in modifying arsenic-related carcinogenesis remains unclear. This study aimed to investigate the potential interaction between urinary arsenic levels and DIGM on bladder cancer risk.MethodsWe conducted a cross-sectional analysis using data from the National Health and Nutrition Examination Survey (NHANES) 2007–2018. Bladder cancer status was obtained through self-reported medical questionnaires. Total urinary arsenic was measured using ICP-DRC-MS, and arsenobetaine was subtracted to estimate toxic inorganic arsenic exposure. DIGM was constructed based on 24-h dietary recall data. Weighted multivariable logistic regression models were used to evaluate associations, and interaction was tested by including a product term (urinary arsenic*DIGM) and assessed on both additive and multiplicative scales.ResultsAmong 4,889 participants (mean age 47.47 years; 50.34% male), 585 had bladder cancer. After adjusting for covariates, elevated urinary arsenic was associated with increased bladder cancer risk (OR: 2.22, 95% CI: 1.53–3.22). Interaction analysis revealed a significant multiplicative interaction between urinary arsenic and DIGM (P-interaction = 0.022). Stratified analysis showed a strong positive association between urinary arsenic and bladder cancer in participants in the lowest DIGM tertile (OR: 1.95, 95% CI: 1.46–2.61). This association was significantly attenuated and became non-significant in those in the highest DIGM tertile (OR: 1.13, 95% CI: 0.89–1.44). Measures of additive interaction (RERI = 0.47, AP = 0.31) further supported a synergistic effect.ConclusionOur findings suggest that a diet promoting a healthier gut microbiota, as indicated by a higher DIGM score, may attenuate the association between urinary arsenic exposure and bladder cancer risk. These results indicate that dietary intervention could be a strategic approach to mitigate urinary arsenic-related cancer risk, highlighting the importance of diet–gut–microbiome interactions in environmental carcinogenesis.